Meta-Analysis of the Core Aroma Components of Grape and Wine Aroma - Ilc, Tina; Werck-Reichhart, Danièle; Navrot, Nicolas (Frontiers in Plant Science, 2016)
Wine aroma strongly influences wine quality, yet its composition and its evolution during the winemaking process are poorly understood. Volatile compounds that constitute wine aroma are traditionally divided into three classes according to their origin: grape, fermentation and maturation aroma. We challenge this view with meta-analysis and review of grape and wine volatiles and their precursors from 82 profiling experiments. We compiled a list of 141 common grape and wine volatiles and quantitatively compared 43 of them. Our work offers insight into complex relationships between biosynthesis of aroma in grapes and the changes during the winemaking process. Monoterpenes are one of the largest and most researched wine aroma compounds. We show that their diversity in wines is mainly due to the oxidative metabolism of linalool in grapes. Furthermore, we demonstrate that most of the linalool produced in grapes is converted to these oxidized derivatives.